(untitled) (Bangladesh Journal of Pharmacology, 2025)
This study aims to isolate and characterize secondary metabolites from the brown algae Dictyota bartayresiana and evaluate its cytotoxicity under in vitro conditions. Phytochemical analyses were extracted using dichloromethane and ethyl acetate as solvents. The results showed the presence of various compounds such as terpenoids, flavonoids, phenols, and alkaloids. Gas chromatography-mass spectrometry was utilized to characterize the extracts. The cytotoxicity evaluation of the crude extracts by MTT assay showed the inhibitory concentration (IC50) for both extracts in the MDA-MB-231 cell line to be 1 µg/mL. The studies in cell biology indicated a change in cell morphology including detached cells with a round morphology, indicating the induction of apoptosis. Wound healing assay showed that both extracts inhibited the invasion of MDA-MB-231 cells (0.75 µg/mL).